The process of coping : an alternative examination : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University - Foster, Helen Marguerite; Foster, Helen Marguerite (Massey University, 1995)
The area of research into coping is complex and challenging and there are no agreed methods to examine the facets of coping behaviour. The present research aimed to capture the complexity of the experience of coping as a multi-faceted, dynamic, flowing phenomenon, and to explore the way people experience the changes that occur over time as a stressful event evolves. Coping was conceptualised as a process which is initiated when a person first becomes aware that she or he is under stress and continues to flow and change until there is an indication that an outcome has been reached. The theoretical framework was based on the transactional perspective of Lazarus and Folkman (1984) and included the concepts of appraisal, coping strategies, reactions and outcome. An alternative methodology was used which corresponded to the theoretical framework and attempted to capture how people coped with stressful events individually and collectively. The analyses provided a finer-grained examination of the entire coping process. Two studies were conducted to examine the coping process over time. In the first study, ten participants reported their experiences of coping with short-term stress in daily stressful events. In the second study, nine women reported their experience of coping with the longer term event of gynaecological surgery. They reported their experiences of coping at five phases: prior to the surgery; during hospitalisation: at two stages of the recovery phase: and following the medical clearance. The results from the first study showed that there was considerable variability in how the participants coped with daily events. In the surgery study it was found that those who had a positive subjective outcome experienced coping as a process differently to those who had a negative subjective outcome. The results from both studies showed that specific patterns of responses between the appraisals, coping strategies, and reactions flowed reciprocally and influenced the outcome. It was found that some patterns were variable. These were considered to be the continual attempts to manage the stressful event, and the effectiveness of these attempts depended on whether the coping process was positive or negative. Other patterns of response appeared to be consistent and these were established in the initial stages. They tended to be maintained over time and were considered to be the main influence in the outcome. When the coping process was generally appraised as positive, then there was a positive outcome. When the coping process was appraised as negative, there were positive attempts at coping but these were outweighed by the negative influences and there was usually a negative outcome. It was concluded that the process of coping is a continually flowing experience which is influenced mainly by cognitive appraisals which are established during the initial stages of a stressful event. It is the specific combinations of appraisals, coping strategies and reactions which constitute the coping process and influence the outcome. The complexity of the experience of coping and specific patterns of responses can be captured in more detail by the use of an alternative methodology which gathers more detailed information and analyses the data at an individual level as well as at the group level. There were limitations to the methodology used and these are discussed, as are future directions for research.
Keywords: Coping; Stress; Surgery recovery